2018
DOI: 10.1080/15438627.2018.1447476
|View full text |Cite
|
Sign up to set email alerts
|

The independent effects of match location, match result and the quality of opposition on subjective wellbeing in under 23 soccer players: a case study

Abstract: This study examined if subjective wellbeing in soccer players was affected by match location, match result and opposition quality before a match (PRE), 1 day after (POST-1), and 3 days after a match (POST-3). Eleven professional male soccer players from the under 23 squad playing in the Premier League 2 division completed a wellbeing questionnaire before and after 17 matches. Match training load (session-rating perceived exertion) was not different, regardless of the location, result, or quality of opposition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
36
4
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 32 publications
7
36
4
2
Order By: Relevance
“…It should also be acknowledged that as is the case with applied sport and the completion of congested schedules (a minimum of two successive bouts of match-play, with an inter-match recovery period of < 96 h), players who are often not fully recovered are required to compete in a subsequent match. The physical and mental demands of these matches can also be further exacerbated by additional confounding factors, such as travelling to and from away matches [10,11], with two-thirds of the players surveyed suggesting that travel is a potential factor that limits their recovery [4]. Furthermore, during these congested periods, it is common for matches to be played during the evening, as such, the timing of matches may affect indices of sleep which may then further exacerbate the recovery time course of a player [12].…”
Section: Key Pointsmentioning
confidence: 99%
“…It should also be acknowledged that as is the case with applied sport and the completion of congested schedules (a minimum of two successive bouts of match-play, with an inter-match recovery period of < 96 h), players who are often not fully recovered are required to compete in a subsequent match. The physical and mental demands of these matches can also be further exacerbated by additional confounding factors, such as travelling to and from away matches [10,11], with two-thirds of the players surveyed suggesting that travel is a potential factor that limits their recovery [4]. Furthermore, during these congested periods, it is common for matches to be played during the evening, as such, the timing of matches may affect indices of sleep which may then further exacerbate the recovery time course of a player [12].…”
Section: Key Pointsmentioning
confidence: 99%
“…duration, time zones), kick-off time, ‘current form’ and changes in own and opponent’s playing systems and tactics should be accounted for where possible to ensure future study designs are in sync with real-world competition scenarios. Recent research in professional [ 22 ] and elite under 23 players [ 23 ] has shown strong associations between match result, opponent standard, and game location and subjective measures of well-being. Similarly, collective data for the team as a whole are also generally reported for these one-match scenarios.…”
Section: Critique Of Current Literature: Research Lacks Relevance Formentioning
confidence: 99%
“…Because self-reported wellbeing may encompass psychological state in addition to physical symptoms, it is possible that the mental fatigue incurred by soccer goalkeepers during match-play (empirical observations) may contribute to these findings. In addition, independent of the degree of physical loading, post-match wellness may be influenced by various situational factors such as opposition quality, match location, and the quality of opposition [63]. Future work should therefore investigate goalkeepers' physiological responses to particular activities within training and match-play to enable physical loads to be appropriately periodised.…”
Section: Conclusion and Directions For Future Researchmentioning
confidence: 99%